Pengaruh Pemanfaatan Aplikasi Youtube dalam Mata Pelajaran PAI sebagai Media Pembelajaran Inovatif pada Era Digital - Nabil Akmal, Muhammad; Arianto, Aji; Badriyah, Laila (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2025)
YouTube is one of the social media platforms widely utilized across various fields, including education. As a learning medium, YouTube offers multiple functions, benefits, and positive impacts that help students understand materials more effectively. The presence of learning media in the teaching and learning process is considered crucial because it acts as an intermediary for delivering materials from teachers to students. Furthermore, learning media make the process more engaging, dynamic, and less monotonous, enabling students to absorb the materials more easily. This study aims to examine the impact of utilizing the YouTube application in Islamic Religious Education (PAI) as an innovative learning medium in the digital era. This research employs a qualitative method with a data analysis technique based on library research. The data sources used include documents, books, magazines, and other relevant materials. In the context of the digital era, advanced technology simplifies various aspects of life, including education. Outdated technologies are replaced with more advanced and beneficial technologies, such as YouTube, which offers a novel approach to delivering teaching materials. The PAI subject, which encompasses faith, morality, the Qur'an, and hadith, plays a significant role in shaping students' guidance for both worldly and hereafter life.